PENGARUH KINERJA KEUANGAN PADA NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Korompis, Khika Indira Putri Hermawan; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The purpose of this study to examine (1) the effect of financial performance on the firm value , (2) the effect of Good Corporate Governance moderating influence of financial performance on the firm value . Independent variables in this study is financial performance. The dependent variable in this study is the firm value. Moderator variables in this study were of Good Corporate Governance.The population of this research is manufacturing companies listed in Indonesia Stock Exchange (IDX) the observation period 2013-2015. The number of samples of this research are 48 companies with 144 observations of data. The samples in this study using purposive non-probability sampling technique by using specific criteria for the selection of the sample. This research data analysis techniques using Moderated Regression Analysis (MRA). The results showed that the financial performance has positive effect on the firm value. Good Corporate Governance weaken the influence of financial performance in the firm value .
Keywords: financial performance, firm value, and Good Corporate Governance